Comparison of Quantum Yield of Upconversion Nanocrystals Determined by Absolute and Relative Methods. Issue 2 (23rd December 2022) - Madirov, Eduard; Busko, Dmitry; Cardona, Fernando Arteaga; Hudry, Damien; Kuznetsov, Sergey V.; Konyushkin, Vasilii A.; Nakladov, Andrey N.; Alexandrov, Alexander A.; Howard, Ian A.; Richards, Bryce S.; Turshatov, Andrey
Abstract : Photoluminescence quantum yield ( ϕ ) is a key parameter of any luminescent material. There are two main ways to determine this value: 1) absolute, which requires calculation of the number of emitted and absorbed photons; and 2) relative, which utilizes the emission of a reference sample with known ϕ . Both methods become more complicated in case of upconversion (UC) photoluminescence, due to its nonlinear nature. The main obstacle to employing the relative method is the lack of a suitable reference with known UC quantum yield (UCQY, ϕ UC ). Herein, a new UCQY reference material is presented, based on SrF2 :1%Yb 3+, 1%Er 3+ single crystal, for the relative measurement of ϕ UC for near‐infrared (976 nm)‐to‐visible UC. When utilizing this reference material, the ϕ UC is determined to be 2.5% (at 100 W cm −2 ) for α‐NaYF4 :18%Yb 3+, 2%Er 3+ @CaF2 nanocrystals (NCs). This result coincides very well with the value for the same NCs determined using the absolute method of ϕ UC  = 2.4% (at 100 W cm −2 ). The intensity dependence of UCQY yield for the NCs determined using the SrF2 :1%Yb 3+, 1%Er 3+ reference exhibits good agreement with the results acquired with the absolute method. In addition, various effects that can have an impact on the measured UCQY using absolute and relative methods are discussed. Abstract : A novel material—SrF2 :1%Yb 3+, 1%Er 3+ single crystal—is proposed as a reference for accurate determination of upconversion quantum yield (UCQY). The performance is tested by measurement of UCQY of α‐NaYF4 :18%Yb 3+, 2%Er 3+ @CaF2 core/shell nanocrystals both in an integrating sphere (the absolute method) and using the relative method with the reference crystal. Good level of conformity is found for both methods.